22. The Effect Of Giving White Pure Ethanol Extract (Allium sativum) On The Growth Of Aeromonas hydrophyla Bacteria In Goldfish (Cypirinus carpio) cultivation - Zikrina Rahmi; Diannita Harahap; Syafrina Sari Lubis; Darmawi Darmawi (Universitas Syiah Kuala, 2019)
This study aimed to determine the effect of garlic extract (Allium sativum) to the growth of Aeromonas hydrophila bacteria. Sample of A. hydrophila was obtained from the Fish Quarantine Station of the Aceh Fisheries Product Quality and Safety Control.Extraction of garlic was conducted by maceration method using ethanol solvent. This study used 6 treatments and consisted of three replications. Treatment I concentration of garlic extract 45%, treatment II with concentration of garlic extract 50%, treatment III concentration 55%, treatment IV concentration 60%. Positive control used chloramphenicol antibiotics and negative control used 96% ethanol. The test results showed that 60% garlic extract (A. sativum) was more effective in inhibiting the growth of A. hydrophila bacteria compared to other concentrations. The lowest effect was owned by 45%. Ethanol extract of garlic (A. sativum)had the ability to inhibit the growth of A. hydrophila because it has antibacterial compounds.